2019
DOI: 10.4093/dmj.2018.0232
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Protein Arginine Methyltransferase 1 in Pancreas Development by Regulating Protein Stability of Neurogenin 3

Abstract: BackgroundProtein arginine methyltransferase 1 (PRMT1) is a major enzyme responsible for the formation of methylarginine in mammalian cells. Recent studies have revealed that PRMT1 plays important roles in the development of various tissues. However, its role in pancreas development has not yet been elucidated.MethodsPancreatic progenitor cell-specific Prmt1 knock-out (Prmt1 PKO) mice were generated and characterized for their metabolic and histological phenotypes and their levels of Neurog3 gene expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In contrast to its high expression in breast cancer ( Wang et al, 2014 ), the greatly repressed expression of PRMT4 in PDAC cells also suggested that the pathogenic roles of PRMT4 in pancreatic cancer might be mediated by tissue-specific signaling mechanisms. In addition, other type I PRMTs such as PRMT1 also critically regulate pancreas development and PDAC pathogenesis ( Wang Y. et al, 2016 ; Lin et al, 2018 ; Lee et al, 2019 ; Song et al, 2020 ), and their pathogenic roles in PDAC cells deserve further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its high expression in breast cancer ( Wang et al, 2014 ), the greatly repressed expression of PRMT4 in PDAC cells also suggested that the pathogenic roles of PRMT4 in pancreatic cancer might be mediated by tissue-specific signaling mechanisms. In addition, other type I PRMTs such as PRMT1 also critically regulate pancreas development and PDAC pathogenesis ( Wang Y. et al, 2016 ; Lin et al, 2018 ; Lee et al, 2019 ; Song et al, 2020 ), and their pathogenic roles in PDAC cells deserve further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the short half-life of NGN3 in both H1 and P- iKO hESCs during in vitro pancreatic endocrine differentiation, observing robust expression in the EP stage that fell abruptly by the EC stage (Figure S2C). Another previous study showed accumulation of NGN3 in the pancreas of P-KO mice from E14.5 to the postnatal stage (Lee et al, 2019). To determine whether P-KO is also associated with NGN3 accumulation in this study, we treated P-iKO cells with dox in the PE stage for 3 d and further differentiated them into EP cells (Figure 3A).…”
Section: Resultsmentioning
confidence: 79%
“…The role of PRMT1-mediated arginine methylation in pancreas development, however, is poorly understood. PRMT1-KO (PKO) mouse embryos exhibit prolonged NGN3 expression accompanied by reduced pancreatic β-cell mass and pancreatic hypoplasia after birth (Lee et al, 2019). This suggests PRMT1 may control NGN3 stability in mammalian pancreatic development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PRMT1 whole-body KO mice are embryonically lethal [ 22 ], conditional KO studies have revealed the important roles of PRMT1 in different cellular processes. For example, the deletion of PRMT1 from the muscular system and neural progenitors leads to the failure of muscle differentiation and brain demyelination, respectively [ 23 , 24 ]. PRMT1 has been considered a key factor in the epigenetic control and maintenance of the expression levels of genes involved in the determination of the functions and identities of mature β-cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%